Handbook of the economics of finance : vol.1A coporate finance - Constantinides, George M.; Harris, Milton; Stulz, René M. (Amsterdam ; Boston : Elsevier/North-Holland, 2003)
Handbook of the Economics of Finance Volume 1A and 1B.The handbooks are intended to provide not only useful reference volumes for professional collections but also possible supplementary readings for advanced courses for graduate students in economics.
Includes bibliographical references and index.
rpm 19/09/16
Loans
Keywords: Finance; Economics; Corporations; Capital assets pricing model